Strategi Komunikasi Kolaboratif Berbasis Partisipasi Pemuda dalam Penguatan Citra Destinasi Wisata di Maluku - Feky Manuputty; Simona Christina Henderika Litaay; Afdhal Afdhal; Nathalia Debby Makaruku (MAN 4 Kota Pekanbaru, 2025)
This study explores collaborative communication strategies based on youth participation in strengthening the destination image of Nam Indah Beach in Ohoitahit Village, North Dullah Island, Maluku. Employing a descriptive qualitative approach, data were collected through observation, interviews, and document analysis. The findings show that the village government’s communication strategies emphasize youth involvement, social media utilization, and collaboration between authorities and community groups. These efforts have enhanced the image of Nam Indah Beach as a destination with strong local identity and ecotourism potential, while fostering residents’ sense of ownership and environmental awareness. The study’s novelty lies in its community-based youth collaboration model that not only strengthens destination branding but also supports social transformation and community empowerment. It recommends improving participatory strategic communication capacity in tourism to enrich discourse in development communication and community-based tourism studies.